Wally's stories - Paley, Vivian Gussin, 1929-2019 (Harvard University Press, 1981)
Publisher's description: Vivian Paley's account of her kindergarten classroom, where children are encouraged to learn by using their fantasies and stories. The book describes the evolution of both teacher and students as they grow to understand each other through this unusual teaching method. The author shows that in the course of creating their own dramatic world, five-year-olds are capable of thought and language far in advance of what they accomplish in traditional classroom exercises.